The Impact of Whistleblowing System on Fraud Prevention, With Bugis Cultural Values as Moderating Factors - Wiliana, Rahayu; Nagu, Nadhirah; Syamsuddin (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
This study aims to assess the influence of two main factors: (1) the implementation of a whistleblowing system to prevent fraud, and (2) the moderating effect of Bugis cultural values on the relationship between the whistleblowing system and fraud prevention. The research was carried out in 13 Regional Work Units (SKPD) situated in Sidenreng Rappang Regency. The research methodology employed a quantitative approach, and the sample was selected using a nonprobability sampling method known as purposive sampling, with a respondent population of 172 individuals. Primary data for this research was collected through the distribution of questionnaires. Statistical analysis was performed using a Structural Equation Model (SEM), and the analysis was conducted using Smart-PLS 3.0 software. The research results indicate that the whistleblowing system has a positive impact on fraud prevention efforts, although Bugis cultural values tend to weaken the influence of the whistleblowing system on prevention.